Human–robot interactions and experiences of staff and service robots in aged care - Valeria Macalupu; Evonne Miller; Lee Martin; Glenda Caldwell (Scientific Reports, 2025)
Abstract The rise of robotics in aged care is transforming how older adults are cared for, addressing staff shortages and workload. Daily interactions with staff and residents highlight an urgent need to better understand and improve human–robot interactions. This study investigates how 34 staff interacted with 10 service robots in a regional Australian aged care facility over 5 years, focusing primarily on their experience with service robots that transported meals and laundry. Guided by the Almere model, the research employs a qualitative case study approach, drawing on observations, focus groups, and interviews with management, industry leaders, and frontline staff. Findings are categorised into Emotional Reactions, Human–Robot Interaction and Collaboration, Social License and Environmental Dynamics. Results indicate conditional acceptance of service robots with scepticism about the service robots’ reliability and practical utility. Our study highlights the importance of a supportive environment, robust infrastructure and adequate training for successful robotic adoption. It also argues for engaging diverse multi-tiered stakeholders in investigating, designing, and implementing robotics in aged care, emphasising the role of social behaviours and interactions for what we propose as functional social service robots.